Coding scheme for defining the behavior of a pedagogical agent (International Journal of Engineering and Computer Science, 2016)
The overall objective of our work is to define the verbal behavior and nonverbal behavior of a pedagogical agent. Our approach is an empirical approach based on the annotation of corpus videos. This approach we have used in several works. In this paper we focus on the annotation scheme that we put in place to define the verbal component of the future agent behavior